Rancangan Media Lightning Tamiya Car untuk Pembelajaran STEM di Sekolah Dasar - Dita Sriadiastuti; Ghullam Hamdu (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2022)
The development of an increasingly modern era, especially in the age of globalization, which demands human resources which is a requirement for development purposes. One of the ways that can be traveled in improving the quality is through education. With the 2013 curriculum applied today, it prioritizes the self-development of students to actively involve themselves in the process of learning. 2013 curriculum According to learning is performed thematically, where learning can be combined with other materials so that students are able to understand the concept of material that is learned to be optimal. These thematic learning can be integrated with scientific approaches that are collaborated with STEM-based learning. Hence the media learning as an intermediate tool in the learning process used to convey information in the learning process between teachers to students in conveying information. It is hoped that we can create more meaningful learning with the development done to one of the learning media. This research uses qualitative methods with descriptive data analysis using FGD (Focus Group Discuss) result data. Based on the FGD data obtained, the design of Lightning Tamiya Car Media is eligible and meets the criteria desired to serve as a learning medium that can be used for STEM-based Learning for the 2013 curriculum.